Novel NOD2 Mutation in Early-Onset Inflammatory Bowel Phenotype. Issue 6 (25th April 2018) - Girardelli, Martina; Loganes, Claudia; Pin, Alessia; Stacul, Elisabetta; Decleva, Eva; Vozzi, Diego; Baj, Gabriele; De Giacomo, Costantino; Tommasini, Alberto; Bianco, Anna Monica
Abstract: Background: Nucleotide-binding oligomerization domain 2 (NOD2) is a key intracellular protein of the innate immune system. NOD2 variants are associated with inflammatory bowel disease (IBD) and other inflammatory phenotypes. We described the case of a baby with a very early-onset IBD who is characterized by a rare homozygous variant in NOD2, found through whole-exome sequencing, Its pathogenic effect was investigated through bioinformatics and functional studies. Methods: The microbicide activity of the patient's phagocytes was analyzed using Escherichia coli . HEK293 and Caco2 cell lines were transfected with wild-type and mutated NOD2 cDNA to evaluate the NF-kB activity and the protein distribution. The functionality of the NOD2 pathway was assessed through analysis of the expression of tumor nectrosis factor alpha (TNFα) on monocytes. The levels of various cytokines were quantified in the patient plasma by a multiplex suspension array. Results: A missense NOD2 mutation, c.G1277A; p.R426H in homozygosis, was found. The patient's microbicide activity was comparable to that observed in controls. HEK293 cells transfected with the mutated cDNA showed a 20-fold increase of NF-kB activation in basal condition. Moreover, Caco2 immunostaining revealed a different cytoplasmic distribution of the mutated protein compared with wild-type. A higher production of TNFα by monocytes and elevated levels of plasmatic cytokines and chemokines were evidenced in the patient. Conclusions: This homozygous mutation is functionally relevant and shows a different NOD2 involvement in the IBD phenotype. In our patient, this mutation caused a gain of function typical of the Blau syndrome phenotype, manifesting, however, an IBD-like phenotype.